The tyrosine phosphatase SHP2 controls TGFβ-induced STAT3 signaling to regulate fibroblast activation and fibrosis - Zehender, Ariella; Huang, Jingang; Gyoerfi, Andrea-Hermina; Matei, Alexandru-Emil; Thuong Trinh-Minh; Xu, Xiaohan; Li, Yi-Nan; Chen, Chih-Wei; Lin, Jianping; Dees, Clara; Beyer, Christian; Gelse, Kolja; et al. (Nature Communications, 2018)
Uncontrolled activation of TGFβ signaling is a common denominator of fibrotic tissue remodeling. Here we characterize the tyrosine phosphatase SHP2 as a molecular checkpoint for TGFβ-induced JAK2/STAT3 signaling and as a potential target for the treatment of fibrosis. TGFβ stimulates the phosphatase activity of SHP2, although this effect is in part counterbalanced by inhibitory effects on SHP2 expression. Stimulation with TGFβ promotes recruitment of SHP2 to JAK2 in fibroblasts with subsequent dephosphorylation of JAK2 at Y570 and activation of STAT3. The effects of SHP2 on STAT3 activation translate into major regulatory effects of SHP2 on fibroblast activation and tissue fibrosis. Genetic or pharmacologic inactivation of SHP2 promotes accumulation of JAK2 phosphorylated at Y570, reduces JAK2/STAT3 signaling, inhibits TGFβ-induced fibroblast activation and ameliorates dermal and pulmonary fibrosis. Given the availability of potent SHP2 inhibitors, SHP2 might thus be a potential target for the treatment of fibrosis.
EVALuna2:34477